2016
DOI: 10.3727/096368915x687688
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved Ex Vivo-Expanded Allogeneic Myeloid Progenitor Cell Product Protects Neutropenic Mice from a Lethal Fungal Infection

Abstract: Severe neutropenia induced by chemotherapy or conditioning for hematopoietic cell transplantation often results in morbidity and mortality due to infection by opportunistic pathogens. A system has been developed to generate ex vivo-expanded mouse myeloid progenitor cells (mMPCs) that produce functional neutrophils in vivo upon transplantation in a pathogen challenge model. It has previously been demonstrated that transplantation of large numbers of freshly isolated myeloid progenitors from a single donor provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Sargramostim’s actions on alveolar macrophages, dendritic cells, and T cells may allow for complementary immune response changes versus increases in cell numbers as seen with other agents such as rhu G-CSF ( Figure 1 ) ( 5 , 11 , 12 , 161 , 162 ). Other novel products, such as hematopoietc stem cell-derived ex vivo -expanded myeloid progenitor cells and phenotypically typed functional granulocytes, have been shown to be efficacious in animal models ( 184 , 185 ).…”
Section: Immune Responses To Infections and Risk Of Gm-csf Insufficiencymentioning
confidence: 99%
“…Sargramostim’s actions on alveolar macrophages, dendritic cells, and T cells may allow for complementary immune response changes versus increases in cell numbers as seen with other agents such as rhu G-CSF ( Figure 1 ) ( 5 , 11 , 12 , 161 , 162 ). Other novel products, such as hematopoietc stem cell-derived ex vivo -expanded myeloid progenitor cells and phenotypically typed functional granulocytes, have been shown to be efficacious in animal models ( 184 , 185 ).…”
Section: Immune Responses To Infections and Risk Of Gm-csf Insufficiencymentioning
confidence: 99%
“…7 To overcome these limitations, administration of ex vivo expanded myeloid progenitors has been explored as a way to facilitate a more rapid myeloid recovery and improve overall survival after myeloablation. [8][9][10][11][12][13][14][15] Myeloid progenitors produced ex vivo from somatic hematopoietic stem/progenitor cells (HSPCs) have been shown to reduce BM aplasia and fungal and bacterial infections and improve overall survival after BM ablation in animal models. [8][9][10][11][12]15 Recent studies have also demonstrated that HSPCs improve survival from sepsis in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Myeloid progenitors produced ex vivo from somatic hematopoietic stem/progenitor cells (HSPCs) have been shown to reduce BM aplasia and fungal and bacterial infections and improve overall survival after BM ablation in animal models. [8][9][10][11][12]15 Recent studies have also demonstrated that HSPCs improve survival from sepsis in a mouse model. 16 The benefits of a progenitor-based strategy are supported by clinical trials demonstrating the safety and feasibility of using non-HLA-matched ex vivo expanded cord blood progenitors as an alternative to granulocyte transfusion in patients with acute myeloid and other leukemias after intensive chemotherapy.…”
Section: Introductionmentioning
confidence: 99%